Dentistry and Optometry: Collaborative Ventures in Health Mission Teams to Address Global Health Challenges - Anna Chandsawangbhuwana; Steven H. Wang (Journal of the California Dental Association)
Background Short-term medical missions (STMMs) have witnessed a surge in participation, particularly among healthcare professionals and trainees from high-income countries (HICs) traveling to lower- and middle-income countries (LMICs) to provide care to underserved populations. Motivations for participation vary, with emotional and professional development cited as primary reasons. However, the effectiveness and long-term impact of STMMs remain inadequately researched, with critiques highlighting the lack of standardized evaluation, potential harm to host communities, and exacerbation of global health inequalities.Interprofessional Education and Collaborative Practice Opportunities The authors advocate for an integration of dental and optometric care within STMMs, considering the significant burden of oral diseases and vision impairment, particularly in LMICs. Dental and optometric professionals not only provide immediate relief but also contribute to health education and prevention efforts, addressing broader health determinants. The authors stress the importance of ethical decision-making, cultural sensitivity, and long-term collaboration with local stakeholders. They further highlight the important roles of interprofessional education and collaborative practice in addressing global health workforce shortages and strengthening healthcare systems. Emphasizing the need for longitudinal engagement and sustainable capacity building, they advocate for collaborative, multidisciplinary approaches focused on measurable community health gains.Practical Implications The authors call for a shift toward collaborative, community-led approaches in STMMs, guided by ethical principles, cultural humility, and a commitment to long-term engagement and capacity building. By fostering partnerships, promoting interprofessional education, and prioritizing local empowerment, STMMs have the potential to contribute meaningfully to global health equity and sustainable development.